Francisco García Bazán, El gnosticismo: esencia, origen y trayectoria, 1ª Ed., Guadalquivir, Buenos Aires, 2009, 235 pág., ISBN: 978-987-22138-6-2 - Martin De Blassi, Fernando (2010)
Fil: Martin De Blassi, Fernando.